They called me mad : genius, madness, and the scientists who pushed the outer limits of knowledge - Monahan, John (Berkley Books, 2010)
"From Dr. Frankenstein to Dr. Jekyll, the image of the mad scientist surrounded by glass vials, copper coils, and electrical apparatuses remains a popular fixture. In films and fiction, he's comically misguided, tragically misunderstood, or pathologically evil. But the origins of this stereotype can be found in the sometimes eccentric real-life men and women who challenged orthodoxy, made waves--and broke new scientific frontiers."--from cover p. 4.